Nanofoaming of PMMA using a batch CO2 process: Influence of the PMMA viscoelastic behaviour. (23rd October 2015) - Forest, C.; Chaumont, P.; Cassagnau, P.; Swoboda, B.; Sonntag, P.
Abstract: Nano-cellular foams were successfully produced from nanostructured PMMA/block copolymer blends using a gaseous CO2 foaming process. The use of block copolymer as potential nucleating agents has allowed the obtaining of nano-cells with cell densities higher than 10 14 cm −3 . Optimization on PMMA matrix formulation composed of blends of PMMAs with different molar masses, combined with the optimization of the foaming stage, resulted in the decrease of the foam density, from about 0.6 to 0.3 g cm −3, while keeping homogeneous foams with nano-cells of an average size lower than 130 nm. It was found that drastic changes in viscoelastic behaviour of PMMA/CO2 system influenced cell growth mechanisms and was the cause of variations of PMMA-based foam nano-structures. Graphical abstract: Highlights: Nano-cellular PMMA/acrylate-based copolymer foams were obtained using a two-stage batch CO2 process. The cell growth is controlled by the extensional viscosity. The balance of entangled and non-entangled PMMA chains allows the control of the cell growth. Nano-cells with an average size lower than 110 nm and with foam densities of about 0.32 g cm −1 were elaborated.